As modalidades do ato e sua singularidade na adolescência - Carla Almeida Capanema (2009)
This study describes about the act of adolescents as an attempt to resolve conflicts caused by the entrance in puberty, body changes and the pulsional exceeding, besides the sharing of parental figures and the encounter with sex, relating them to anguish. Many young people express, in the absence of symbolic references that support this singular moment, appearances not related with a symptom, but an act. In this work it was developed modes of action: "passing to the act" and "acting out", committed by the subject in response to their discomfort experienced, added to Lacanian definition that every true act carries a violation. The adolescence raises the act as something that marks a before and an after, a crossing. Often the act is an attempt to register, and when serial activity becomes routine, making it necessary to recover the function of the act when trivializing has been deleted it off. Only the own adolescent can repair your act since that a reference to the symbolic is can become possible. Through clinical cases, it is a theoretical analysis of illegal acts committed by adolescents in socio-educational reinsertion and assisted by Liberty Assisted Program - important place where young people can speak of his act, betting that this act might be something modifier, providing a subjective rectification. According as this perspective, the real "infringement" act is beside of public authority, in a program whose dimension of individual singularity is taken into account beyond the universalizing policy, becoming available to face this situation so banal observed in social field